(untitled) (Research, Society and Development, 2020)
To verify the level of knowledge of parents and guardians about dentistry in early childhood, and to analyze sociodemographic variables. This was a field research, observational and cross-sectional with quantitative approach and descriptive and analytical analysis of the data, through questionnaires, which were applied to parents / guardians of children from 0 to 3 years old from municipal daycare centers a city of the Paraíba hinterland. 171 parents or guardians of children enrolled in municipal public day care centers were interviewed. Most of them were predominant females (91.2%), aged 15 to 30 years (63.2%), with monthly family income of up to R 780.00 (67.3%), and had predominant education level of elementary school I (33.9%). Most parents / guardians (55.6%) considered that oral health meant hygiene and were aware of the existence of dentistry for babies (64.9%). For 52.6% of respondents, the ideal time to start hygiene of the baby’s oral cavity is from the birth of the first tooth and on the method used to perform this hygiene, 53.8% indicated gauze or diaper soaked in filtered water. It was observed that 53.8% reported that the importance of oral hygiene is related to the overall health of the baby. Parents and /or guardians of public daycare infants centers demonstrated a reasonable knowledge regarding children’s oral health.